CXCL10/IP10 is a novel potential in vitro marker of TB infection - Ilaria Sauzullo; Valeria Belvisi; Fernanda Chiarini; Miriam Lichtner; Claudio Maria Mastroianni; Fabio Mengoni; Raffaella Rossi; Vincenzo Vullo (Microbiologia Medica, 2009)
Introduction IFN-γ is a pivotal cytokine in the immune response to Myc. tuberculosis, infact this is the key cytokine produced in response to antigens specific following tuberculosis exposure causing either active or latent tuberculosis (TB) and this observation forms the basis of interferon gamma release assay (IGRA), but there are alternative or additional cytokines and chemokines that could be used to improve detection of Myc. tuberculosis infection.The aim of this study was to evaluate the diagnostic utility of chemokine CXCL10/IP-10 as biomarker of active TB and to compare the results with classical QuantiFERON-Gold assay . Methods CXCL10/IP-10 and IFN-γ responses to stimulation with ESAT-6 and CFP-10 were evaluated in 21 patients with active tuberculosis and in 6 healthy unexposed subjects with no history of TB or TB contact were used as controls healthy controls. QuantiFERON-TB Gold (QFT-G, Cellestis) was used for the measurement of IFN-γ levels; CXCL10/IP-10 was detected by ELISA (R&D Systems ). Results Of the 21 TB patients included, 11 had a QFT-G positive and 10 had negative QFT-G results.All QFT-G positive patients had increased levels of CXCL10/IP-10 (median, pg/ml) in both ESAT-6 and CFP-10 stimulated samples patients compared to healthy controls (1807 and 1111 vs 251 and 188 of controls, respectively) (p<0.001 for both). The patients with active TB and QFT-G negative exhibited higher concentrations of CXCL10/IP-10 following antigen stimulation (837 pg/ml for ESAT-6;1674 pg/ml for CFP-10) (p<0.001). Conclusion Our study showed that in all patients with active TB, the CXCL10/IP-10 is expressed in higher amounts than IFN-γ following Myc. tuberculosis antigen-specific stimulation, and CXCL10/IP-10 appeared to be even more sensitive than QuantiFERON TB-Gold in TB patients with negative IFN-γ response. The measurement of chemokine CXCL10/IP-10, although not specific for tuberculosis, may have potential as an alternative or additional marker to IFN-γ in vitro diagnosis infection with Myc. tuberculosis.